The effect of hydrocortisone and methylphenidate on the growth of murine L929 fibroblast and chick brain neuronal cells - Pretorius, Etheresia (University of Pretoria, 2013)
Dissertation (MSc (Anatomy))--University of Pretoria, 2009.